2015
DOI: 10.1021/acs.inorgchem.5b01025
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Catalase Reaction: Dioxygen Activation via Two-Electron Transfer from Hydroxide to Dioxygen Mediated By a Manganese(III) Salen Complex

Abstract: Although atmospheric dioxygen is regarded as the most ideal oxidant, O2 activation for use in oxygenation reactions intrinsically requires a costly sacrificial reductant. The present study investigated the use of aqueous alkaline solution for O2 activation. A manganese(III) salen complex, Mn(III)(salen)(Cl), in toluene reacts with aqueous KOH solution under aerobic conditions, which yields a di-μ-oxo dimanganese(IV) salen complex, [Mn(IV)(salen)]2(μ-O)2. The (18)O isotope experiments show that (18)O2 is indeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
2
9
1
Order By: Relevance
“…Indeed, the pH‐controlled protonation or deprotonation of the phenolic groups gives the possibility to obtain compounds with different numbers of metal centres and coordination geometries, giving rise to synthesis of homometallic or heterometallic complexes . These compounds are also of interest for their catalytic properties and as models of biological systems …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the pH‐controlled protonation or deprotonation of the phenolic groups gives the possibility to obtain compounds with different numbers of metal centres and coordination geometries, giving rise to synthesis of homometallic or heterometallic complexes . These compounds are also of interest for their catalytic properties and as models of biological systems …”
Section: Introductionmentioning
confidence: 99%
“…[19] These compounds are also of interest for their catalytic properties [20] and as models of biological systems. [21][22][23] Herein we report the synthesis, structure, electronic and magnetic properties of a trinuclear mixed-valence Co II,III complex using acetate and a derivative of H 2 Salen, namely N,N'-bis(salicylidene)-2-hydroxy-1,3-propanediamine, abbreviated H 3 L hereafter, where H represents dissociable hydroxy H atoms. The structure refinement of this complex, [Co 3 (HL) 2 (m-AcO) 2 (AcO) 2 ] proved to be challenging, because of the very low scattering power of the crystallized sample.…”
Section: Introductionmentioning
confidence: 99%
“…Autoreduction of a metal complex is not necessarily limited to the porphyrin system, but was also reported for a bis­(benzene-1,2-dithiolato) copper­(III) complex . Another interesting example is an antimony­(V) porphyrin bearing hydroxide axial ligands, which is reduced upon photoirradiation. , I also reported that the reaction of a manganese­(III) salen complex with aqueous alkaline solution yields a manganese­(II)–manganese­(III) dimer …”
Section: Introductionmentioning
confidence: 79%
“…Although oxidoreductases capable of direct interaction with O 2 in its triplet ground state have been identified [85], the majority of native oxidase enzymes requires additional organic cofactors or redox-active transition metal centers Molecular oxygen from air is a clean, abundant and environmentally benign reagent ideally suited for substrate oxidation processes including selective C-H bond functionalization. Therefore the utilization of oxidase-like reactivity for green synthetic processes based on O 2 or H 2 O 2 is a highly desirable research goal [92][93][94].…”
Section: Activation and Reduction Of Dioxygenmentioning
confidence: 99%